Pengaruh Capital Intensity, Sales Growth, dan Kepemilikan Institusional terhadap Tax Avoidance - Fitria Eka Ningsih; Calosa Melina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The purpose of this research is to offer hard data on how factors like capital intensity, sales growth, and institutional ownership affect tax avoidance. Using a quantitative methodology, this research compiles secondary data from financial reports made available on the website of the Indonesian Stock Exchange. This analysis covers the years 2020–2024 and focuses on property and real estate companies that are listed on the Indonesia Stock Exchange. The researchers in this study used the Purposive Sampling technique to choose their sample. Of the 96 businesses that made up the study's population, 15 were able to pass the selection criteria and be included in the final sample. Multiple linear regression with descriptive statistics, panel data regression model analysis, the Fixed Effect Model as the model selection test, multiple linear tests, hypothesis testing with data processing using Eviews software version 12, and classical assumption tests were the methods used for hypothesis testing. Tax avoidance is impacted by Institutional Ownership, Capital Intensity, and Sales Growth all at once, according to the findings of the simultaneous hypothesis test. The findings of the partial hypothesis testing indicate that tax avoidance is not affected by capital intensity or institutional ownership, but it is affected by sales growth.